Dataset of Boeng Sneh Community Fisheries (CFi), Boeng Ream Community Fish Refuge (CFR) and Tasoung Irrigation Scheme - Sithirith, Mak; Sok, Sao (2024)
The data was collected in two of Cambodia’s Mekong Delta Provinces, namely, Prey Veng and Takeo, as well as in Kampong Thom-a province located in the Tonle Sap Lake (TSL) region. The researchers utilized both qualitative and quantitative methods to gather primary and secondary data from the studied sites. The primary data were obtained through key informant interviews (KIIs) and focus group discussions (FGDs).